(untitled) - Stern, Anita (Đà Nẵng, 2003)
Each story in World Folktales explores a common theme in the lives of people everywhere; birth and chidhood, challenge and edventure, love and marriage, or death and inheritance.
Keywords: Folk literature,Văn học dân gian